Current Genetic Epidemiology of 𝛽-Thalassemias and Structural Hemoglobin Variants in the Lazio Region (Central Italy) Following Recent Migration Movements - Antonio Amato; Maria Pia Cappabianca; Alessia Colosimo; Maria Perri; Paola Grisanti; Ivo Zaghis; Donatella Ponzini; Maria Lerone (Advances in Hematology, 2010)
The aim of this study was to describe the changing pattern of mutational spectrum of 𝛽-thalassemia (𝛽-thal) in the Lazio region (Central Italy), as consequence of recent demographic variations. From 1994 until present, 256 immigrant subjects with hemoglobin disorders (including 191 heterozygotes and 65 homozygotes or compound heterozygotes) coming from 44 different foreign countries, have been molecularly characterized. 14 𝛽-globin gene mutations were identified and their frequencies reflect different ethnic origins: 8 of these mutations account for 76.97% of all molecular defects, while 6 of them are much rare, representing less than 2% of the total. These data differ, both in type and percentage, from the mutational spectrum detected in the native population in 1995. Since a few defects are prevalent in each country, a proper strategy for the identification of mutations in immigrant individuals relies on the prior knowledge of their frequency in native ethnic group.